Analysis of Intraoperative Radiographic Electrode Placement During Cochlear Implantation. Issue 6 (July 2015) - Gnagi, Sharon H.; Baker, Trenton R.; Pollei, Taylor R.; Barrs, David M.
Abstract : Objective: To investigate the clinical value of intraoperative plain radiographs in determining correct placement of cochlear implants. Patients: All cochlear implant insertions over a 10-year period by a single surgeon. Interventions: Cochlear implantation with intraoperative imaging. Main Outcome Measure: Whether intraoperative imaging affects clinical/surgical management. Results: A consecutive retrospective review of 207 cochlear implantations performed in 187 patients was performed. All implants performed had intraoperative plain film imaging. Etiology of hearing loss, surgical variations, gender, age, and implant type did not affect intraoperative imaging. Four cases were identified where variations in intraoperative imaging interpreted by the surgeon warranted further discussion. In one patient, the intraoperative x-ray interpretation missed an incorrectly placed electrode. Postoperative CT scan confirmed implant electrode within the superior semicircular canal. In three patients, intraoperative x-ray results aided management by confirming surgical findings; however, no subsequent clinical or surgical alterations were made based on imaging. One of these three patients experienced a noticeable function decline postoperatively that correlated with altered positioning of the cochlear implant on intraoperative radiographs. In all surgeries, no changes were made to the electrode placement based on the intraoperative radiographs. Conclusion: Intraoperative plain film imaging during cochlear implantation, although commonly employed, does not typically affect clinical management. For select cases, imaging may continue to be useful based on the surgeon's discretion and intraoperative findings for confirmatory purposes.